Dangerous beauty [videorecording (DVD)] - McCormack, Catherine, 1972-; Sewell, Rufus, 1967-; Platt, Oliver; Ward, Fred, 1942-; Bisset, Jacqueline, 1944-; Rosenthal, Margaret F. (Twentieth Century Fox Home Entertainment, 2015)
Based on the true story of Veronica Franco, the woman who defied convention in 16th-century Venice.